Systematic review and bayesian network meta-analysis: comparative efficacy and safety of six commonly used biologic therapies for moderate-to-severe Crohn’s disease - Su, Haohang; Xiao, Shengwei; Liang, Zhiqing; Xun, Tianrong; Zhang, Jinfang; Yang, Xixiao (Frontiers in Pharmacology, 2025)
BackgroundIn contrast to previous network meta-analysis using classical frequentist methods, we evaluated the efficacy and safety of six frequently-used biologics through a Bayesian method.MethodsWeb of Science, Scopus, CENTRAL, ClinicalTrials.gov and ICTRP were searched to collect randomized controlled trials (RCTs) in adults with moderate-to-severe Crohn’s disease, comparing Infliximab, Adalimumab, Certolizumab pegol, Ustekinumab, Risankizumab, or Vedolizumab, relative to placebo or an active comparator for induction of clinical response (two different definitions) and maintenance of clinical remission. A random-effects model was performed with rankings according to the surface under cumulative ranking curve (SUCRA) probability. Finally, we completed sensitivity and consistency analyses, and evaluated the certainty of evidence through GRADE working group guidance.ResultsWe identified 22 and 20 RCTs for induction and maintenance therapy, respectively. Infliximab combined with azathioprine was most effective for inducing clinical response in TNF (tumor necrosis factor) antagonist-naïve patients. For TNF antagonist-experienced patients, Ustekinumab (SUCRA 86.19) and Risankizumab (SUCRA 62.56) have the largest SUCRA in induction of clinical response. Risankizumab has the lowest risk of adverse events (SUCRA 84.81), serious adverse events (SUCRA 94.23), and serious infections (SUCRA 79.73) in induction therapy. Adalimumab and the 10 mg/kg regimen of Infliximab rank highest for maintaining clinical remission.ConclusionThis analysis suggests that Infliximab in combination with azathioprine may be preferred biologic agents for induction therapy in TNF antagonist-naïve patients. For TNF antagonist-experienced patients, Ustekinumab and Risankizumab may be preferred biologic agents for induction therapy. Risankizumab potentially has the lowest safety risk worth exploring in induction therapy. Adalimumab and the 10 mg/kg regimen of Infliximab have maintenance efficacy benefits for responders to induction therapy.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=458609, Identifier CRD42023458609.